The solubility of 40Ar and 84Kr in liquid hydrocarbons: Implications for Titan's geological evolution. Issue 12 (27th June 2013) - Hodyss, Robert; Choukroun, Mathieu; Sotin, Christophe; Beauchamp, Patricia
Abstract [1] The solubility of argon and krypton in methane and ethane has been experimentally determined at Titan‐relevant temperatures. At typical Titan surface temperature (94 K), argon and krypton solubilities are very large (47% in methane and 15% in ethane for Ar, 29% in methane and 43% in ethane for Kr), making liquid alkanes on Titan an important potential reservoir of 40Ar and other noble gases. Large subsurface reservoirs of liquid ethane and methane could be sufficient to trap much of the argon outgassing from Titan's interior, which can help explain the discrepancy between the potential amount of 40Ar produced inside Titan's interior and the amount observed in the atmosphere by Cassini‐Huygens. Consequently, on Titan, liquid hydrocarbons may function as a buffer in the outgassing of volatiles from the interior, and they may strongly influence the evolution of the atmosphere's composition through the release of soluble gases upon evaporation and/or intake upon condensation.